Oxford Scholarship Online 2018
DOI: 10.1093/oso/9780198793380.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Euroscepticism and the Future of European Integration

Abstract: The European Union (EU) is facing one of the rockiest periods in its existence. At no time in its history has it looked so economically fragile, so insecure about how to protect its borders, so divided over how to tackle the crisis of legitimacy facing its institutions, and so under assault by Eurosceptic parties. The unprecedented levels of integration in recent decades have led to increased public contestation, yet at the same the EU is more reliant on public support for its continued legitimacy than ever be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
346
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 403 publications
(354 citation statements)
references
References 0 publications
8
346
0
Order By: Relevance
“…While these approaches have greatly contributed to our understanding of public support and scepticism towards the EU, they provide us with little guidance about how the outcome of the Brexit vote might affect public support for Europe. As I have argued elsewhere (De Vries, ), public opinion towards the EU is best understood with reference to benchmarks. My benchmark theory suggests that people's attitudes towards Europe are ultimately rooted in a comparison, namely a comparison between the benefits of the current status quo of membership with those associated with an alternative state of one's country being outside the EU.…”
Section: Public Opinion Towards the Eu: Understanding The Role Of Brexitmentioning
confidence: 99%
See 1 more Smart Citation
“…While these approaches have greatly contributed to our understanding of public support and scepticism towards the EU, they provide us with little guidance about how the outcome of the Brexit vote might affect public support for Europe. As I have argued elsewhere (De Vries, ), public opinion towards the EU is best understood with reference to benchmarks. My benchmark theory suggests that people's attitudes towards Europe are ultimately rooted in a comparison, namely a comparison between the benefits of the current status quo of membership with those associated with an alternative state of one's country being outside the EU.…”
Section: Public Opinion Towards the Eu: Understanding The Role Of Brexitmentioning
confidence: 99%
“…This has already proven an important touchstone of dissent within electoral campaigns in some member states and was a central issue in the Brexit campaign (Clarke et al ., , see also Kriesi et al ., ). Other perceived costs that have been highlighted by eurosceptic pundits are that countries have to accept the jurisdiction of the European Court, or engage in some forms of financial guarantees, transfer payments or debt relief efforts, for example, through membership in the eurozone (De Vries, ).…”
Section: Public Opinion Towards the Eu: Understanding The Role Of Brexitmentioning
confidence: 99%
“…Why exposure to the vignette triggered a response to financial aid but not to cooperation in other policy areas is an important area for future research. I have suggested that this may be due to the largely transactional nature of public opinion (De Vries, ), but the extent to which this is the case will be an important avenue for further investigation. The evidence provided here also raises interesting questions about how perceptions of a shared European history may help us to understand the contours of public opinion towards European integration and the conditions under which they do.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that people benchmark the alternative state by extrapolating from current national conditions, specifically national economic performance and quality of government (De Vries, ). Similarly, the alternative state can be benchmarked based on previous precedents of other countries leaving, especially the UK's experiences with Brexit (De Vries, , ). Support for European integration and cooperation is higher when people think that they or their country would be worse off under the alternative state scenario.…”
Section: Historical Narratives and Public Opinion Towards European Inmentioning
confidence: 99%
“…This is why those who fear the shift towards 'existential' (or constitutional) euroscepticism should be especially attuned to 'policy euroscepticism' (De Vries, 2018). This is all the more true if we believe that the EU's illadaptability to shocks is due to bad policies rather than bad constitutional design.…”
Section: Order-contestationmentioning
confidence: 99%